2004
DOI: 10.1002/jtr.468
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural tourist behaviour: a replication and extension involving Hofstede's uncertainty avoidance dimension

Abstract: Hofstede's five cross-cultural dimensions have been broadly applied in the literature. Money and Crotts recently applied the dimension of uncertainty avoidance to a matched sample comprised of low uncertainty avoidance German and high uncertainty avoidance Japanese tourists, finding their behaviours consistent with those behaviours predicted by Hofstede. This study both replicates and extends their research across a representative sample of first time leisure visitors to the USA representing 58 nations. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(147 citation statements)
references
References 26 publications
8
128
0
3
Order By: Relevance
“…However as discussed in literature, Epistemic values are very important to satisfy and encourages to revisit. In past literature it was found that adventure seeking behaviour such as risk taking and exploring out of safer boundaries gives personal satisfaction (Sibthorp, et al, 2007; and for travelers who enjoy in different cultures learning and experiencing the world and finds pleasure from it (Litvin, et al, 2004;. The difference in finding could be that the past research are carried out among luxury hotels and Yachts and tourists who stay in Guesthouses could be different.…”
Section: Discussionmentioning
confidence: 99%
“…However as discussed in literature, Epistemic values are very important to satisfy and encourages to revisit. In past literature it was found that adventure seeking behaviour such as risk taking and exploring out of safer boundaries gives personal satisfaction (Sibthorp, et al, 2007; and for travelers who enjoy in different cultures learning and experiencing the world and finds pleasure from it (Litvin, et al, 2004;. The difference in finding could be that the past research are carried out among luxury hotels and Yachts and tourists who stay in Guesthouses could be different.…”
Section: Discussionmentioning
confidence: 99%
“…The UK also has much higher levels of masculinity than Portugal. Research addressing national culture comparisons typically include countries representing different levels of one or more cultural dimensions (Litvin et al 2004). Thus, these countries were considered relevant for conducting a comparison to evaluate the influence of the cultural characteristics on social media use for travel purposes A similar procedure to select countries for cross-cultural research has been conducted in other studies (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, this framework is considered to be the most comprehensive national cultural framework in cross-cultural studies (Litvin et al 2004;Hsu et al 2013) and can be used to explain and predict behaviors (Hofstede 1980). In Hofstede (1980) original work, country cultures were categorized into four groups according to: power distance (PDI), individualism versus collectivism (IDV), masculinity versus femininity (MAS), uncertainty avoidance (UAI).…”
Section: Cultural Dimensions and Social Mediamentioning
confidence: 99%
See 2 more Smart Citations